2018
DOI: 10.1111/pcmr.12741
|View full text |Cite
|
Sign up to set email alerts
|

A PAX3/BRN2 rheostat controls the dynamics of BRAF mediated MITF regulation in MITFhigh/AXLlow melanoma

Abstract: The BRAF kinase and the MAPK pathway are targets of current melanoma therapies. However, MAPK pathway inhibition results in dynamic changes of downstream targets that can counteract inhibitor‐action not only in during treatment, but also in acquired resistant tumours. One such dynamic change involves the expression of the transcription factor MITF, a crucial regulator of cell survival and proliferation in untreated as well as drug‐addicted acquired resistant melanoma. Tight control over MITF expression levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…1a). PAX3, a transcription factor recently shown to function in a rheostat model with BRN2 to control MITF expression, was detected in all three cell lines 21 irrespective of MITF level (Fig. 1a).…”
Section: Brn2 Expression Reduces Cell Proliferationmentioning
confidence: 86%
“…1a). PAX3, a transcription factor recently shown to function in a rheostat model with BRN2 to control MITF expression, was detected in all three cell lines 21 irrespective of MITF level (Fig. 1a).…”
Section: Brn2 Expression Reduces Cell Proliferationmentioning
confidence: 86%
“…It has to be noted that some other transcriptional factors are also involved in MITF activation in the formation of BRAFi resistance in melanoma. Paired box 3 (PAX3) is a classic transcriptional inducer of MITF and is necessary for the up-regulation of MITF induced by BRAF/MEK inhibition 42 . Cadherin-associated protein beta 1 (β-catenin) is another known transcription factor that regulates the expression of MITF 43 .…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that downregulation of MITF is the consequence of a known pathway, in which MAPK activation phosphorylates the transcription factor and targets it to degradation [27]. In contrast, UM-164 inhibited ERK and caused activation of MITF, an effect that may reduce the long term impact on cell proliferation and contribute to the development of drug resistance as described for BRAF- and MEK inhibitors [28]. Analysis of biopsies from BRAF V600E melanoma patients following relapse with vemurafenib, or combination of dabrafenib and trametinib revealed upregulation of several lineage-specific transcription factors including MITF [29].…”
Section: Discussionmentioning
confidence: 99%